Relational resources, digital capability, and value proposition innovation: impact on entrepreneurial performance in Chinese snack enterprises - Haibo Li; Ang, Hong Loong; Noor Fzlinda Fabeil (MDPI, 2025)
This paper aims to conduct an empirical study on the influence of relational resources (RR) and digital capability (DC) on entrepreneurial performance (EP), as well as to examine the mediating role of value proposition innovation (VPI). This research seeks to fill the gap in the existing literature regarding the impact of relational resources and digital capability on entrepreneurial performance. Data were collected from 191 respondents from small snack food production enterprises in China. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed to analyze and measure both direct and indirect effects and to test the hypothesized model. The findings indicate that while relational resources and digital capability do not have a significant positive influence on entrepreneurial performance, they significantly positively influence value proposition innovation, which in turn has a significant positive effect on entrepreneurial performance. Therefore, value proposition innovation fully mediates the relationship between relational resources, digital capability, and entrepreneurial performance. This study contributes to resolving the ongoing debate on the influence of relational resources and digital capability on entrepreneurial performance.